2004
DOI: 10.1093/oxfordjournals.schbul.a007083
|View full text |Cite
|
Sign up to set email alerts
|

Factorial Composition of Self-Rated Schizotypal Traits Among Young Males Undergoing Military Training

Abstract: The aim of this study within the Athens Study of Psychosis Proneness and Incidence of Schizophrenia (ASPIS) was the examination of the latent structure of schizotypal dimensions among a large population of young male conscripts in the Greek Air Force during their first week of military training. Confirmatory factor analysis (CFA) was conducted on 1,355 reliable responders to the self-rated Schizotypal Personality Questionnaire (SPQ), which covers all nine aspects of DSM-III-R schizotypal personality disorder (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
187
2
12

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(221 citation statements)
references
References 103 publications
18
187
2
12
Order By: Relevance
“…Specifically, five models proposed in the literature (Kendler et al, 1991;Raine et al, 1994;Seiver and Gunderson, 1983;Stefanis et al, 2004;Wuthrich and Bates, 2006), depicted in Figure 1, as well as five models hierarchically related to several of these, were examined. Several indices were selected a priori to assess the fit of measurement models to the data.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Specifically, five models proposed in the literature (Kendler et al, 1991;Raine et al, 1994;Seiver and Gunderson, 1983;Stefanis et al, 2004;Wuthrich and Bates, 2006), depicted in Figure 1, as well as five models hierarchically related to several of these, were examined. Several indices were selected a priori to assess the fit of measurement models to the data.…”
Section: Discussionmentioning
confidence: 99%
“…Both exploratory (Calkins et al, 2004;Gruzelier et al, 1996) and confirmatory (Chen et al, 1997;Raine et al, 1994;Reynolds et al, 2000) factor analyses have suggested that the SPQ comprises these three factors. However, recent studies have demonstrated other factor structures (Stefanis et al, 2004;Wuthrich and Bates, 2006). Two other traditional schizotypy scales were administered so that their correlations with the derived SPQ domains could be examined.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Factor analytic studies of schizotypy traits have shown at least three components: negative, positive and disorganization dimensions [3][4][5][6][7][8] . Similarly, factor analytic studies in schizophrenia have reliably shown that psychotic symptoms can be grouped into positive, negative and disorganization dimensions [9][10][11][12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%